Output power limitations and improvements in passively mode locked GaAs/AlGaAs quantum well lasers - Tandoi, G.; Ironside, Charlie; Marsh, J.; Bryce, A. (2012)
We report a novel approach for increasing the output power in passively mode locked semiconductor lasers. Our approach uses epitaxial structures with an optical trap in the bottom cladding that enlarges the vertical mode size to scale the pulse saturation energy. With this approach we demonstrate a very high peak power of 9.8 W per facet, at a repetition rate of 6.8 GHz and with pulse duration of 0.71 ps. In particular, we compare two GaAs/AlGaAs epilayer designs, a double quantum well design operating at 830 nm and a single quantum well design operating at 795 nm, with vertical mode sizes of 0.5 and 0.75 µm, respectively. We show that a larger mode size not only shifts the mode locking regime of operation toward higher powers, but also produces other improvements with respect to two main failure mechanisms that limit the output power, catastrophic optical mirror damage and catastrophic optical saturable absorber damage. For the 830-nm material structure, we also investigate the effect of nonabsorbing mirrors on output power and mode locked operation of colliding pulse mode locked lasers. © 2006 IEEE.